INDUSTRI HALAL DALAM PERSPEKTIF EKONOMI ISLAM - Siti Harizah; Mohammad Usman (IZZI: Jurnal Ekonomi Islam, 2022)
The halal industry is a process of processing goods based on sharia guarantees, so that the products they produce are good (thayib), healthy, safe and not harmful, therefore halal to be consumed, enjoyed or used. The concept of halal does not only stay away from substances that cannot be consumed (haram) but also includes safety and quality aspects related to the processing, handling, equipment used, storage, packaging, transportation and distribution. The concept of halal is not merely a religious concept but is understood as a comprehensive quality concept. With the potential for the development of the halal industry, management is very much needed in order to maintain the existence of the halal industry. In addition, it is necessary to study Islamic law regarding the management of the halal industry, one of which is related to Islamic economics. Because we all know that industrial activities are activities that are included in the economic realm. In this study using qualitative research methods, the data sources used are the theological discourse of the halal economy and industry as well as articles in journals related to the theme. The data collection technique was carried out by means of a literature review. The results of this study are: Islam encourages its people to participate and participate in various forms of economic activity, agriculture, plantation management, fisheries, industry and trade.